Functionalization of orange waste with phosphoric group for Anion separation - Ghimire, Kedar Nath (Journal of Nepal Chemical Society, 2013)
A novel adsorbent, Phosphorylated Orange Juice Residue, POJR, has been investigated. The extent of phosphorylation was measured with the aid of fluorescence X-ray crystallography, which indicates that the degree of phosphorylation is 1.2. The POJR has very high binding affinity for ferric ion. Also bound ferric ions selectively adsorb anions like arsenite, arsenate, selenite, selenate, antimonate and phosphate. DOI: http://dx.doi.org/10.3126/jncs.v29i0.9275 Journal of Nepal Chemical Society Vol. 29, 2012 Page: 110-112 Uploaded date: 12/6/2013